Ethnoornithological study in selected villages of Riau Province, Indonesia - ELFIS; Prima Wahyu Titisari; NUNUT SUHARNI; KHAIRANI; NADIATUL JANNA; TIKA PERMATASARI; INDRY CHAHYANA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Elfis, Titisari PW, Suharni N, Khairani, Janna N, Permatasari T, Chahyana I. 2020. Ethnoornithological study in selected villages of Riau Province, Indonesia. Biodiversitas 21: 1645-1652. Riau Province, along the central-eastern coast of Sumatra, is an area of high bird diversity. The purpose of this study is to document and analyze the ethnoornithological local wisdom of some selected villages and use it to develop a strategy for biodiversity conservation in Riau. The method used in this research involved direct observation of some areas that have local accumulated natural history knowledge and interviews with selected informants of the local community. Some bird species were found to be central to the local culture, and these included the Punai Saluang/Sumatran Green-pigeon (Treron oxyura Temminck), Serindit Melayu/Blue-crowned Hanging Parrot (Loriculus galgulus Linnaeus), Bubut/Greater Coucal (Centropus Sinensis Stephens), and Rangkong Gading/Helmeted Hornbill (Rhinoplax vigil Forster). These bird species are used in traditional medicine, rituals and symbols in Riau Province. Serindit Melayu/Blue-crowned Hanging Parrot is a symbol of the Malay community in Riau and averts evil in the village of Gema. Rangkong Gading/Helmeted Hornbill body parts are used in ritual treatment to cure various diseases by the TalangMamak Tribe in Rantau Langsat. Punai Saluang/Sumatran Green-pigeon is used as a metaphor in folk literature of the Malays in the Pelalawan area, and Bubut/Greater Coucal (Centropus sinensis Stephens) body parts are used as traditional medicine by the Malays in Kuok Village. There are several aspects that need to be studied further to conserve these birds, including the ecology, reproduction, and behavior aspects. Through preservation of these ethnoornithological rituals and education of the younger generation, these and other species of birds can be better sustained in and around the culture of Riau society.